Delivering a new helicopter base at Kai Tak for the Hong Kong Government Flying Service. Issue 1 (19th September 2022) - Mak, George; Lo, Jeffrey; Lam, Rom
Abstract : An additional helicopter base has been built for Government Flying Service at the former Kai Tak airport runway site in Hong Kong. The base allows high-rise development to take place at Tung Chung new town near the service's existing base at Hong Kong International airport, which would have restricted emergency helicopter operations during poor weather. The project involved construction of a take-off and landing pad, parking bays and hangar for two helicopters, plus an office building for the flight planning centre and air command and control centre. This paper describes how use of an NEC contract helped ensure close collaboration between the employer and contractor, leading to timely completion with zero accidents despite restrictions caused by the Covid-19 pandemic.